1997
DOI: 10.1017/s1742758400016441
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies interference of oviposition behaviour in the cowpea weevils Callosobruchus rhodesianus (Pic) and Callosobruchus maculatus (F.)

Abstract: The total number of eggs laid by Callosobruchus rhodesianus (Pic.) and Callosobruchus maculatus (F.) females in the presence of single and mixed species populations of males at different densities were counted. Increasing male density significantly reduced the realised fecundity of C. maculatus but not C. rhodesianus females. In the presence of C. maculatus males, however, the number of eggs laid by C. rhodesianus was greatly reduced. The reduction in egg laying and observations on mating behaviour indicates d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
(8 reference statements)
0
7
0
Order By: Relevance
“… 15 , 68 70 ]. As a result, it should be easier to detect demographic RI when the starting frequencies of species are highly skewed because fitness loss from RI will be amplified when the rarer species experiences proportionally more harmful heterospecific encounters [ 70 72 ]. Consequently, our experimental design is conservative with respect to being able to detect demographic RI, which likely explains why we observed demographic RI for only some experimental treatments.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 68 70 ]. As a result, it should be easier to detect demographic RI when the starting frequencies of species are highly skewed because fitness loss from RI will be amplified when the rarer species experiences proportionally more harmful heterospecific encounters [ 70 72 ]. Consequently, our experimental design is conservative with respect to being able to detect demographic RI, which likely explains why we observed demographic RI for only some experimental treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming reciprocal reproductive interference between two closely related species, relatively more abundant species inflicts stronger effect on the fitness of the other species (Giga and Canhão 1997;Liu et al 2007;Kishi et al 2009), because as the number of individuals increases, harassing males become more abundant. In addition, increased conspecific abundance is advantageous for females, because it dilutes the effect of mating attempts by heterospecifics on individual females (Kyogoku and Nishida 2012).…”
Section: Consequences Of Reproductive Interferencementioning
confidence: 99%
“…The C. maculatus larvae could eliminate C. rhodesianus larvae after larval fights or could inhibit the development of its competitor. The ability of C. maculatus to inhibit the oviposition of C. rhodesianus (Giga & Canhao, 1997) and the reduced chances of survival of C. rhodesianus larvae in interspecific competition still decreased the developmental capacities of this species under storage conditions. In interspecific competition with Callosobruchus chinensis , C. maculatus also appears to be the better competitor, and several studies have demonstrated its ability to exclude its competitor in mixed cultures (Bellows, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Interspecific competition with the sympatric species C. maculatus could be a disadvantage for C. rhodesianus. Giga & Canhao (1997) observed that the number of eggs laid by C. rhodesianus was greatly reduced in the presence of males of C. maculatus. They suggested that the ability of the latter species to inhibit oviposition of C. rhodesianus could explain its superiority in interspecific competition.…”
Section: Introductionmentioning
confidence: 99%